INSTRUCTIONAL MODEL COACHING FOR NURSING STUDENTS: GUIDELINES FOR SIMULATION - Grace C. Arcamo, Jason R. Lim, and Jeanette P. Lim, (Chelonian Research Foundation, 2024)
Abstract: The study assessed the Instructional Model Coaching for various procedures and identified special areas for the Bachelor of Science in Nursing program. The assessment focused on several areas, including the profile of the respondents in relation to specific variables, namely: the clinical instructor's evaluation of the level of competency of BSN students undergoing pre-clinical simulation and actual practice, as well as the clinical practice involving human-patient simulators. The performance of BSN students in nursing procedures was also evaluated based on semi-structured assessments. The study utilized the descriptive correlational method. Moreover, the findings revealed that among the four areas of assignment, the Delivery Room, with 7-10 years of experience, had the highest number of periods supervising BSN students compared to the other areas. Most respondents attended orientation programs that enabled them to manipulate models and utilize updated electronic instructional materials. These programs, which included training in effective and suitable simulated environments, allowed them to conduct demonstrations for assigned groups of BSN students and to implement return training programs using instructional models. A noticeable difference was observed among BSN students in their nursing procedures during pre-clinical simulations, with better performance observed during actual clinical field practice. In addition, there is a significant relationship between the level of competence and the actual performance of the students. In conclusion, the assessment of clinical performance after exposure to simulation using a human-patient simulator showed that BSN students, as noted by the clinical instructors (respondents), achieved an almost perfect execution of nursing procedures.